Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Ekonomi Siswa Kelas X SMA Pertiwi 1 Padang - Nabila Astri Jelita; Marwan (Jurnal Salingka Nagari, 2026)
This study aims to analyze the effect of the "Make a Match" cooperative learning model on the economics learning outcomes of Grade X (Phase E) students at SMA Pertiwi 1 Padang. The study was motivated by low economics learning outcomes, evidenced by the high percentage of students who had not yet met the Learning Objective Achievement Criteria (KKTP). This situation highlights the need for a learning model capable of enhancing student engagement during the learning process. The study employed a quantitative approach using a quasi-experimental method and a Non-Equivalent Control Group Design. The population consisted of 153 Grade X (Phase E) students at SMA Pertiwi 1 Padang. Samples were selected using purposive sampling: Class X E4 served as the experimental class and Class X E2 as the control class, with 30 students in each. Data collection was conducted through learning outcome tests, specifically pre-tests and post-tests. Data analysis included normality tests, homogeneity tests, and an Independent Sample t-Test. The results indicate a difference in learning outcomes between the experimental and control classes following the intervention. Hypothesis testing yielded a significance value of 0.000 (<0.05), demonstrating that the "Make a Match" cooperative learning model significantly influences the economics learning outcomes of Grade X (Phase E) students at SMA Pertiwi 1 Padang. The "Make a Match" model serves as a viable instructional alternative capable of increasing student engagement while strengthening their understanding of economic concepts.